1994
DOI: 10.1136/gut.35.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability in patients with Crohn's disease and ulcerative colitis and their first degree relatives.

Abstract: Increased intestinal permeability in patients with Crohn's disease and their first degree relatives has been proposed as an aetiological factor. The nine hour overnight urinary excretion of polyethyleneglycol-400 (PEG-400) and three inert sugars (lactulose, I-rhamnose, and mannitol) was used to test the permeation in 47 patients with Crohn's disease of whom 18 had at least one first degree relative with inflammatory bowel disease (2BD) and 52 patients with ulcerative colitis of whom 16 had at least one first d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
104
1
3

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(110 citation statements)
references
References 22 publications
2
104
1
3
Order By: Relevance
“…Similar findings have been shown by Soderholm et al [23] . While Munkholm [32] and Jogerson et al [21] found a negative correlation of age with the absorption of mannitol and excretion of 51 CrEDTA, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been shown by Soderholm et al [23] . While Munkholm [32] and Jogerson et al [21] found a negative correlation of age with the absorption of mannitol and excretion of 51 CrEDTA, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…DCA, the other secretory bile acid, also has an extremely low aqueous concentration in the cecum because of its insolubility (2). Thus (37)(38)(39)(40)42).…”
Section: Discussionmentioning
confidence: 99%
“…If this occurs, CDCA would also enter the mucosa via the paracellular pathway and interact directly with the basolateral membrane of the enterocytes, as well as with mast cells. In conditions of intestinal inflammation, in which both intestinal permeability and the number of mucosal mast cells might be expected to be elevated (37)(38)(39)(40), the tissue might be expected to respond to much lower concentrations of CDCA present in the colonic contents.…”
Section: Discussionmentioning
confidence: 99%
“…Ulcerative colitis and Crohn's disease alter intestinal permeability [25], allowing systemic exposure to antigens that would otherwise be excluded. Gastrointestinal alteration has similarly been noted in undifferentiated spondyloarthropathy [26].…”
Section: Journal Of Infectious Diseases and Preventive Medicinementioning
confidence: 99%